Analisis Kesalahan Siswa dalam Memecahan Masalah pada Materi Sistem Pertidaksamaan Linear Dua Variabel - Erma Yanti; Yuli Amalia; Rahmat Fitra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematics learning at the high school level still shows various problems, especially in students' mathematical problem-solving abilities on the material of two-variable linear inequality systems, which is characterized by many student errors in solving problems in the form of problem solving. This study aims to identify the types of errors made by class X students of SMA and the factors causing errors in solving mathematical problems on the material. This study uses a qualitative approach with a descriptive method, with the research subjects being class X students of. Data collection was conducted through written tests and interviews, while data analysis included data reduction, data presentation, and conclusion drawing. Analysis of student errors was based on Polya's problem-solving stages combined with the Newman Procedure. The results showed that students made four types of errors: errors in understanding the problem, errors in creating a solution plan, errors in implementing the plan, and errors in rechecking the final answer. The most dominant error occurred at the stage of implementing the plan with a percentage of 59.1%, while the least error occurred at the stage of understanding the problem at 17%. Factors causing errors included a lack of understanding of the basic concepts of two-variable linear inequality systems, an inability to transform contextual problems into mathematical models, weak skills in drawing graphs and determining the solution region, and students' low habit of rechecking their answers. Based on these findings, it can be concluded that student errors are conceptual and procedural in nature, so mathematics learning is recommended to emphasize conceptual understanding, strengthening procedural skills, and the habit of reflection and rechecking in the process of mathematical problem solving.